Reformoptionen: Die keine sind - Franz Ruland (Wirtschaftsdienst, 2024)
– In the German pension debate, reform options are repeatedly proposed that are doomed to failure right from the start as they cannot be legally implemented to begin with. One of these is the inclusion of civil servants in the German state pension scheme. This option, however, is prohibited by the German Constitution. Another example is the inclusion of self-employed persons. This demand cannot be met as many freelancers are unable to pay their full contributions. Inflation adjustment of pensions would mean too much of a burden for women as well as for the sick and the disabled. Redistributing money from pensioners with high benefits to pensioners with a low pension would not be conducive, either. Not only would this mean an infringement of the principle of equality, but also there are too few high pensions to redistribute.
Keywords: H55; J11; J26; 330; Rentenpolitik; Rentenreform; Deutschland; Rentenpolitik; Rentenreform; Deutschland